Area Studies at the Crossroads Knowledge Production after the Mobility Turn - Mielke, Katja; Hornidge, Anna-Katharina (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2017)
XXIII, 363 p. 13 illus., 6 illus. in color.